Defects materials of Institut Lavoisier-125(Ti) materials enhanced photocatalytic activity for toluene and chlorobenzene mixtures degradation: Mechanism study - Zhang, Xiaodong; Gao, Bin; Rao, Renzhi; Bi, Fukun; Li, Chenyu; Yue, Ke; Wang, Yuxin; Xu, Jingcheng; Feng, Xiangbo; Yang, Yiqiong (Journal of colloid and interface science, 2024)
[Display omitted] •Defects were introduced in MIL-125 to narrow the forbidden band width.•Improved the surface acidity of material for efficient degradation of mixed VOCs.•Revealed the catalytic mechanism using in situ DRIFTS spectroscopy and GC–MS. In this paper, the effect of three monocarboxylic acids on MIL-125 synthesis was systematically investigated and the results were discussed in detail. X-ray diffractometry (XRD) and nitrogen adsorption–desorption curves indicated that small molecule acids (acetic acid, propionic acid and butyric acid) affected the morphology of MIL-125 and induced lamellar pores and structural defects in the crystals. Thermogravimetric measurements confirmed the presence of acid-regulated defective metal–organic frameworks (MOFs). Electrochemical tests and density function theory calculations indicated that acid modulation could change the forbidden bandwidth of the material. The acid modification strategy effectively promoted the transfer of photogenerated electrons and enhanced the adsorption and activation of O2 and H2O molecules, generating reactive radicals. The modified MOFs also showed excellent performance in the removal of mixed toluene and chlorobenzene. The degradation pathways of the mixture were analyzed by in situ infrared (IR) and gas chromatography-mass spectrometry (GC–MS). The mixture was converted to chlorophenolic intermediates in the presence of reactive oxygen species, further decomposed to form ethers and ethanol, and finally formed small molecules such as carbon dioxide and water. A feasible method was provided for the preparation of photocatalysts for the treatment of mixed VOCs.